Observing protein dynamics during DNA-lesion bypass by the replisome - Wilkinson, Elise M.; Spenkelink, Lisanne M.; van Oijen, Antoine M. (Frontiers in Molecular Biosciences, 2022)
Faithful DNA replication is essential for all life. A multi-protein complex called the replisome contains all the enzymatic activities required to facilitate DNA replication, including unwinding parental DNA and synthesizing two identical daughter molecules. Faithful DNA replication can be challenged by both intrinsic and extrinsic factors, which can result in roadblocks to replication, causing incomplete replication, genomic instability, and an increased mutational load. This increased mutational load can ultimately lead to a number of diseases, a notable example being cancer. A key example of a roadblock to replication is chemical modifications in the DNA caused by exposure to ultraviolet light. Protein dynamics are thought to play a crucial role to the molecular pathways that occur in the presence of such DNA lesions, including potential damage bypass. Therefore, many assays have been developed to study these dynamics. In this review, we discuss three methods that can be used to study protein dynamics during replisome–lesion encounters in replication reactions reconstituted from purified proteins. Specifically, we focus on ensemble biochemical assays, single-molecule fluorescence, and cryo-electron microscopy. We discuss two key model DNA replication systems, derived from Escherichia coli and Saccharomyces cerevisiae. The main methods of choice to study replication over the last decades have involved biochemical assays that rely on ensemble averaging. While these assays do not provide a direct readout of protein dynamics, they can often be inferred. More recently, single-molecule techniques including single-molecule fluorescence microscopy have been used to visualize replisomes encountering lesions in real time. In these experiments, individual proteins can be fluorescently labeled in order to observe the dynamics of specific proteins during DNA replication. Finally, cryo-electron microscopy can provide detailed structures of individual replisome components, which allows functional data to be interpreted in a structural context. While classic cryo-electron microscopy approaches provide static information, recent developments such as time-resolved cryo-electron microscopy help to bridge the gap between static structures and dynamic single-molecule techniques by visualizing sequential steps in biochemical pathways. In combination, these techniques will be capable of visualizing DNA replication and lesion encounter dynamics in real time, whilst observing the structural changes that facilitate these dynamics.